Numerical investigation of erosion due to particles in a cavitating flow in pelton turbine - Lešnik, Luka (Strojniški vestnik, 2025)
Erosion of Pelton turbine components due to cavitation and particle-laden flow is a major challenge in hydropower applications, particularly in sediment-rich river environments. This study presents a numerical investigation on how solid particles contribute to the erosion of a Pelton runner. Computational fluid dynamics (CFD) simulations were conducted using ANSYS CFX 2023 R2, incorporating a Lagrangian particle tracking approach and the Finnie abrasion model to predict erosion patterns under varying sediment concentrations. The results indicate that, under normal sediment conditions, particle erosion does not significantly contribute to blade tip damage. However, under extreme sediment loading, the predicted erosion patterns closely match real-world observations, particularly at the blade tip.
Keywords: cavitation; CFD računalniška dinamika tekočin; CFD simulation; erozija zaradi trdnih delcev; kavitacija; Pelton turbine; Peltonova turbina; solid particle erosion